2011
DOI: 10.1297/cpe.20.39
|View full text |Cite
|
Sign up to set email alerts
|

A Report of Three Girls with Antithyroid Drug-Induced Agranulocytosis; Retrospective Analysis of 18 Cases Aged 15 Years or Younger Reported between 1995 and 2009

Abstract: Agranulocytosis is an extremely serious, although rare, adverse effect of antithyroid drugs (ATDs), including methimazole (MMI) and propylthiouracil (PTU), in children and adolescents. There are few reports about the characteristics of ATD-induced agranulocytosis in Japanese children and adolescents. This report presents the cases of three girls with ATD-induced agranulocytosis and a retrospective analysis of 18 patients with ATD-induced agranulocytosis, whose cases had been referred to the drug manufacturer, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…The lag time to response to G-CSF suggests degree of depletion of committed myeloid progenitors and indeed pluripotent stem cells. Consistent with this, prior observations have shown that growth factors are not effective in cases with severely low ANC (\100) [15]. Bone marrow recovery from agranulocytosis after G-CSF treatment can be delayed when pretreatment bone marrow M:E ratio is \0.5 (mean, 9.8 days) compared to patients who had a M:E ratio C0.5 (mean, 2.2 days) [16].…”
Section: Discussionsupporting
confidence: 72%
“…The lag time to response to G-CSF suggests degree of depletion of committed myeloid progenitors and indeed pluripotent stem cells. Consistent with this, prior observations have shown that growth factors are not effective in cases with severely low ANC (\100) [15]. Bone marrow recovery from agranulocytosis after G-CSF treatment can be delayed when pretreatment bone marrow M:E ratio is \0.5 (mean, 9.8 days) compared to patients who had a M:E ratio C0.5 (mean, 2.2 days) [16].…”
Section: Discussionsupporting
confidence: 72%
“…Although cross‐reactivity among ATD is common, PTU was used as alternative treatment for patients with CMZ/MMI‐induced agranulocytosis . Our sensitivity analysis excluding PTU showed the pooled ORs by risk of HLA‐B*27:05 and HLA‐B*38:02 were much increased in cases excluding PTU‐induced agranulocytosis, suggesting HLA‐B*27:05 and HLA‐B*38:02 may be more specific to CMZ/MMI‐induced agranulocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Data were pooled separately by study design using random-effects model; the inverse variance technique was used for pooling of measures of effects Data were pooled separately by study design using random-effects model; the inverse variance technique was used for pooling of measures of effects agranulocytosis 36. Our sensitivity analysis excluding PTU showed thepooled ORs by risk of HLA-B*27:05 and HLA-B*38:02 were much increased in cases excluding PTU-induced agranulocytosis, suggesting HLA-B*27:05 and HLA-B*38:02 may be more specific to CMZ/MMI-induced agranulocytosis.…”
mentioning
confidence: 99%
“…Review of the literature of reported cases of agranulocytosis between 1999 and 2013 identified 80 cases where the presenting symptoms were described [13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37]. Fever (93.8%), sore throat (68.7%) and chills (21.2%) were the commonest presenting symptoms.…”
Section: Resultsmentioning
confidence: 99%